Pengaruh Corporate Brand Image terhadap Kepuasan Nasabah di PT Bank Syariah Indonesia KC Gorontalo - Bantali, Wilyani; Radji, Djoko Lesmana; Abdussamad, Zulfia K (Economic Reviews Journal, 2024)
This study aims to determine the extent of the influence of Corporate Brand Image on Customer Satisfaction at PT Bank Syariah Indonesia KC Gorontalo. The sampling technique used is purposive sampling, with a sample size of 100 respondents calculated using the Slovin formula. Data collection in this study is done through questionnaires distributed among the population of PT Bank Syariah Indonesia KC Gorontalo. The analysis tool used is simple linear regression. The research findings indicate that Corporate Brand Image has a significant influence on Customer Satisfaction, with a significance level of 0.000 < 0.005. The t-test results show that the calculated t-value is higher than the critical t-value, 7.516 > 1.984. Furthermore, the R-square value is 0.697, indicating that 69.7% of the variation in Customer Satisfaction at PT Bank Syariah Indonesia KC Gorontalo can be explained by Corporate Brand Image, while the remaining 30.3% is influenced by other variables not examined in this study.